Pengelolaan Sampah Dalam Rangka Daur Ulang Melalui Bank Sampah Resik Becik Kelurahan Krobokan, Kota Semarang - Mamun, Afriyani; Khasanah, Khasanah; Sari, Siti Nurindah (Manalisih: Jurnal Penelitian, Sosial, dan Humaniora, 2023)
Waste management must be carried out continuously and involve community members. The objectives of this study are: (1) To find out the stages of community empowerment through the activity of recycling waste at the Krobokan Kelurahan RESIK Garbage Bank Semarang City (2) To find out the benefits felt by the surrounding community after the waste recycling activities are carried out at the Kelurahan Becik Resik Bank. Krobokan City of Semarang. This type of research uses qualitative research, with the informant of the Director of the Rocking Rocking Bank, the manager of the RESIK KARANT Bank and Krobokan Kelurahan Garbage Bank. Data collection techniques using observation, documentation and interview methods. Data Analysis In this study using the interactive analysis model consists of data reduction, data presentation and drawing conclusions. The results showed that the community in its implementation, the garbage bank program provides creative space to improve and create a better life to the community, in addition there are stages carried out by the community, namely the stages of planning, disposal and distribution and mutual cooperation in cleaning the environment. The benefits felt by the surrounding community after the waste recycling activities at the RESIK KARANT Bank is the first awareness. Awareness is a tool and also the purpose of the implementation of every program of Bank ASMPAH RESIK BECIK, because without the awareness and pacifications of the community the activity program will not run. With the presence of a rushing banking bank in Krobokan Village, 40 % of inorganic waste is reduced and can be used as processed handicrafts, then 70 % of organic waste that cannot be processed because the community is first taught to grow croping or planting in its yard, the second is economic contribution . The RESIK THROUGH BECIK Waste Bank also minimizes waste in the environment so that it is beneficial for citizens to become an economic value craft produced from the sale of waste